Dynamic Measurement of Four-Axle Railway Wagon - Svoboda, Martin; Soukup, Josef (Manufacturing Technology Journal, 2013)
This article describes the determination of geometric, mass and stiffness parameters of the individual part of plateau wagon. After measurements were taken the position change of the chassis of the vehicle body and wheel when driving the vehicle over obstacles was observed. The obstacles were formed by wedges. Experimental detection of parameter has been used in the analytical investigation of kinematically excited system of three-body space flexibly stored and linked.
Keywords: railway vehicles; dynamic measurements; vertical oscillation; unbalance